The Analysis of Quick Reading Skills Using Skimming Techniques in Thematic Learning at Grade III Students SD Negeri 01 Ulak Karang - Putri, Lisa; Oktira, Yona Syaida; Efrina , Gusnita; Ayunis, Ayunis (The Future of Education Journal, 2024)
This research aims to analyze fast reading skills through the skimming technique in thematic learning of class III students at SD Negeri 01 Ulak Karang. This research was motivated by students' slowness in understanding a text, students' lack of interest in reading, students' slowness in finding the main idea of ​​a text quickly and the application of less varied learning methods. Therefore, this research aims to analyze fast reading skills through the skimming technique in thematic learning of class III students at SD Negeri 01 Ulak Karang. This research uses a qualitative approach with a descriptive type. Then data is collected through observation, interviews and documentation. Next, data analysis was carried out through three stages, namely: data reduction, data presentation and conclusion drawing. The subjects of this research were class III teachers and class III students. Based on research on the ability to read quickly through the skimming technique of class IIId students at SD Negeri 01 Ulak Karang before conducting the research, many of the students could not read fast, let alone find the main idea in a text, after researchers applied the skimming technique when reading fast, it was found that class IIId students at SD Negeri 01 Ulak Karang there have been changes regarding speed reading skills through skimming techniques